2012
DOI: 10.1371/journal.pone.0043842
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of EGFR Mutation Testing Methods in Lung Carcinoma: Direct Sequencing, Real-time PCR and Immunohistochemistry

Abstract: The objective of this study is to compare two EGFR testing methodologies (a commercial real-time PCR kit and a specific EGFR mutant immunohistochemistry), with direct sequencing and to investigate the limit of detection (LOD) of both PCR-based methods. We identified EGFR mutations in 21 (16%) of the 136 tumours analyzed by direct sequencing. Interestingly, the Therascreen EGFR Mutation Test kit was able to characterize as wild-type one tumour that could not be analyzed by direct sequencing of the PCR product. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 53 publications
4
73
0
Order By: Relevance
“…Angulo et al [35] and Marchetti et al [36] analyzed FFPE material and reported mutation frequencies of 16.2% and 24.1% respectively, a detection rate relatively close to our FFPE set. Therefore we assume that our mutation detection approach is not the reason why such a low mutation frequency was detected in cytological smear samples.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Angulo et al [35] and Marchetti et al [36] analyzed FFPE material and reported mutation frequencies of 16.2% and 24.1% respectively, a detection rate relatively close to our FFPE set. Therefore we assume that our mutation detection approach is not the reason why such a low mutation frequency was detected in cytological smear samples.…”
Section: Discussionsupporting
confidence: 81%
“…As reported in literature, generally preferred tumor material for molecular EGFR analysis and detection of somatic mutations is FFPE tumor tissue [35,36]. However, in case of lung tumors, availability of such material may be limited due to tumor location and many technical limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such selection of patients with NSCLC promoted a better treatment strategy for both high and low EGFR mutations abundant tumors. [30][31][32][33] Further quantification of staining scores in mutation-positive NSCLC has been assessed, and high staining score has been associated with a significant longer progression-free survival in mutation-positive patients as compared with low staining score. 31 A study in which the randomization to EGFR tyrosine kinase inhibitors would be based on the method used for demonstrating an activating EGFR mutation might give clinical relevant information regarding the significance of the amount of EGFR-mutated cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the large number of total EGFR mutations (over 1,300 EGFR mutation entries in COSMIC) and partly explains the ever-growing importance of EFGR mutations in lung cancer (11). The mutation which selected in this research was A763_Y764insFQEA in exon 20.…”
Section: Molecular Detection Of Egfr Mutation In Lung Cancermentioning
confidence: 99%